(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article highlights information about the system, types, history of the formation of documents in the field of technical regulation of the construction TRC of the Republic of Uzbekistan, information about the competent government bodies for their development and approval. as well as the current state of documents in the field of TRC, based on the experience of foreign and developed countries, the results of the analysis of the situation are highlighted. Conclusions are drawn on issues aimed at solving the identified current problems.